Do output contractions trigger democratic change? - Paul J. Burke; Andrew Leigh (Institute for the Study of Labor (IZA), 2010)
Does faster economic growth increase pressure for democratic change, or reduce it? Using data for 154 countries for the period 1963-2007, we examine the short-run relationship between economic growth and moves toward and away from greater democracy. To address the potential endogeneity of economic growth, we use variation in precipitation, temperatures, and commodity prices as instruments for a country's rate of economic growth. Our results indicate that more rapid economic growth reduces the short-run likelihood of institutional change toward democracy. Output contractions due to adverse weather shocks appear to have a particularly important impact on the timing of democratic change.
Keywords: D72; N40; O17; 330; Economic growth; democratization; weather; commodity prices; Wirtschaftswachstum; Demokratisierung; Rohstoffpreis; Wetter; Schätzung; Welt